Exclusive p[rho]0 meson photoproduction with a leading neutron at HERA - Andreev, Vladimir; Bolz, Arthur; Huber, Florian; Radescu, Voica; Sauter, Michel David; Schöning, André (The European physical journal. C, Particles and fields, 2016)
A first measurement is presented of exclusive photoproduction of $$ρ ^0$$ρ0mesons associated with leading neutrons at HERA. The data were taken with the H1 detector in the years 2006 and 2007 at a centre-of-mass energy of $$\sqrt{s}=319$$s=319 GeV and correspond to an integrated luminosity of 1.16 pb$$^{-1}$$-1. The $$ρ ^0$$ρ0mesons with transverse momenta $$p_T<1$$pT<1 GeV are reconstructed from their decays to charged pions, while leading neutrons carrying a large fraction of the incoming proton momentum, $$x_L>0.35$$xL>0.35, are detected in the Forward Neutron Calorimeter. The phase space of the measurement is defined by the photon virtuality $$Q^2 < 2$$Q2<2 GeV$$^2$$2, the total energy of the photon-proton system $$20 < W_{γ p}< 100$$20<Wγp<100 GeV and the polar angle of the leading neutron $$θ _n < 0.75$$θn<0.75mrad. The cross section of the reaction $$γ p → ρ ^0 n π ^+$$γp→ρ0nπ+is measured as a function of several variables. The data are interpreted in terms of a double peripheral process, involving pion exchange at the proton vertex followed by elastic photoproduction of a $$ρ ^0$$ρ0meson on the virtual pion. In the framework of one-pion-exchange dominance the elastic cross section of photon-pion scattering, $$σ ^el(γ π ^+ → ρ ^0π ^+)$$σel(γπ+→ρ0π+), is extracted. The value of this cross section indicates significant absorptive corrections for the exclusive reaction $$γ p → ρ ^0 n π ^+$$γp→ρ0nπ+.